2021
DOI: 10.1002/smtd.202100763
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Neurostress Drives Osteoblastic Exosomal MiR‐21 Transfer to Disrupt Bone Homeostasis and Promote Osteopenia

Abstract: (2 of 16)www.advancedsciencenews.com www.small-methods.com MiR-21 Deficiency Retards ISO-Induced Osteopenia and Affects the Bone Remodeling BalanceNext, we investigated whether miR-21 indeed contributed to the sympatho-adrenergic regulation of bone. To investigate this

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 69 publications
2
36
0
Order By: Relevance
“…Notably, in a recent study, we have shown that sympathetic regulation of the skeleton is mediated through osteoblast-osteoclast miR-21 communication via exosomes, 22 but the core concept underlying sympathetic regulation of bone remains consistent with previous reports, i.e. osteoblastic response represents as crucial and dominant.…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…Notably, in a recent study, we have shown that sympathetic regulation of the skeleton is mediated through osteoblast-osteoclast miR-21 communication via exosomes, 22 but the core concept underlying sympathetic regulation of bone remains consistent with previous reports, i.e. osteoblastic response represents as crucial and dominant.…”
Section: Introductionsupporting
confidence: 88%
“…According to our previous reports, miR-21 deficiency affects the bone remodeling balance and preserves bone homeostasis against multiple extrinsic factors. 22 24 In this study, we further revealed that with only osteoclastic expression of miR-21, osteopenia developed under the ISO challenge (Fig. S2b, c ) due to stimulated osteoclastic bone resorption with remained bone formation or the osteoblastic parameters (Fig.…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations